Influence of symptom burden on physical activity among patients with atrial fibrillation: The chain-mediating roles of exercise sensitivity and kinesiophobia - JianMei Wu; ChunYun Pu; Li Zhang (PLoS ONE, 2026)
Objective Grounded in an integrated fear-avoidance and cognitive-behavioural framework, this study aimed to examine the independent and sequential mediating roles of exercise sensitivity and kinesiophobia in the relationship between symptom burden and physical activity in patients with atrial fibrillation. Methods This cross-sectional study recruited 533 patients with atrial fibrillation from five tertiary hospitals in Chongqing, China, between April and October 2024 using convenience sampling. Symptom burden was assessed using the University of Toronto Atrial Fibrillation Severity Scale (symptom subscale), exercise sensitivity with the Exercise Sensitivity Questionnaire, kinesiophobia with the Tampa Scale for Kinesiophobia Heart, and physical activity with the International Physical Activity Questionnaire-Short Form. Data were analysed using SPSS 25.0, and chain-mediation analysis was performed with the PROCESS macro (Model 6, 5000 bootstrap resamples). Results Symptom burden was significantly and directly associated with reduced physical activity (accounting for 37.00% of the total effect). Three significant indirect pathways were identified: through exercise sensitivity alone (27.60% of the total effect), through kinesiophobia alone (16.17%), and sequentially through exercise sensitivity and kinesiophobia (19.22%). The total indirect effect accounted for 62.99% of the total effect; the 95% bootstrap confidence intervals for all indirect effects did not contain zero. Conclusion Exercise sensitivity and kinesiophobia were identified as statistically significant independent and sequential mediators between symptom burden and physical activity in patients with atrial fibrillation. These results suggest that routine screening and interventions addressing these psychological factors may be beneficial in atrial fibrillation management.